Cost Reduction Associated with Comprehensive Medication Reviews in a Student-Run Free Clinic - Katie Trotta; Randall Moore; Teresa Wells (Journal of Student-Run Clinics, 2020)
Background: Patients taking multiple medications are at increased risk for drug-drug interactions, adverse drug effects, and increases in drug costs. Patients of low socioeconomic status and health literacy have further risk for experiencing these unwanted effects. This study aimed to determine if student-pharmacist led comprehensive medication reviews (CMRs) for patients of a student-run free clinic on multiple chronic medications decreased drug costs and inappropriate overprescribing of medications. Secondary objectives included determination of most overprescribed medication classes and the number and types of recommendations made by student-pharmacists.Methods: Student-pharmacists conducted CMRs on consenting patients seen during a weekly student-run free clinic at a rural university clinic. Included patients were taking six or more chronic medications for two or more chronic disease states at the start of the visit. Information from patient interviews was used to make drug therapy recommendations to interprofessional student teams and an attending provider. Accepted recommendations were implemented into patients’ care plans. The average 30-day drug costs of patients’ medications before and after receiving a CMR were calculated using average wholesale prices and compared using paired t-tests. The most common drug classes recommended to be deprescribed and the total number of accepted recommendations (in the categories of safety, efficacy, and indication) were collected from forms used during CMR.Results: A total of 31 CMRs were completed during the study period, with 92 recommendations made by students and 91% of recommendations accepted by the attending. Average drug costs for a 30-day supply of medication decreased from $698.16 pre-CMR to $619.31 post-CMR, a cost reduction of $78.85 (p = 0.049). The most common recommendations made by students were removal of an unnecessary drug (N = 27), dose too low (N = 15), and additional drug needed (N = 13). The two most overused classes of medications were selective serotonin reuptake inhibitors and proton pump inhibitors.Conclusions: Student-pharmacist led CMRs conducted in a rural free clinic population resulted in a significant decrease in drug spending and identification of drug therapy problems.